Plasma neurofilament light chain in the presenilin 1 E280A autosomal dominant Alzheimer's disease kindred: a cross-sectional and longitudinal cohort study. Issue 6 (June 2020) - Quiroz, Yakeel T; Zetterberg, Henrik; Reiman, Eric M; Chen, Yinghua; Su, Yi; Fox-Fuller, Joshua T; Garcia, Gloria; Villegas, Andres; Sepulveda-Falla, Diego; Villada, Marina; Arboleda-Velasquez, Joseph F; Guzmán-Vélez, Edmarie; et al.
Summary: Background: Neurofilament light chain (NfL) is a promising biomarker of active axonal injury and neuronal degeneration. We aimed to characterise cross-sectional and longitudinal plasma NfL measurements and determine the age at which NfL concentrations begin to differentiate between carriers of the presenilin 1 ( PSEN1 ) E280A (Glu280Ala) mutation and age-matched non-carriers from the Colombian autosomal dominant Alzheimer's disease kindred. Methods: In this cross-sectional and longitudinal cohort study, members of the familial Alzheimer's disease Colombian kindred aged 8–75 years with no other neurological or health conditions were recruited from the Alzheimer's Prevention Initiative Registry at the University of Antioquia (Medellín, Colombia) between Aug 1, 1995, and Dec 15, 2018. We used a single molecule array immunoassay and log-transformed data to examine the relationship between plasma NfL concentrations and age, and establish the earliest age at which NfL concentrations begin to diverge between mutation carriers and non-carriers. Findings: We enrolled a cohort of 1070 PSEN1 E280A mutation carriers and 1074 non-carriers with baseline assessments; of these participants, longitudinal measures (with a mean follow-up of 6 years) were available for 242 mutation carriers and 262 non-carriers. Plasma NfL measurements increased with age in both groups (p<0·0001), and began to differentiate carriers from non-carriers when aged 22 years (22 years before the estimated median age at mild cognitive impairment onset of 44 years), although the ability of plasma NfL to discriminate between carriers and non-carriers only reached high sensitivity close to the age of clinical onset. Interpretation: Our findings further support the promise of plasma NfL as a biomarker of active neurodegeneration in the detection and tracking of Alzheimer's disease and the evaluation of disease-modifying therapies. Funding: National Institute on Aging, National Institute of Neurological Disorders and Stroke, Banner Alzheimer's Foundation, COLCIENCIAS, the Torsten Söderberg Foundation, the Swedish Research Council, the Swedish Alzheimer Foundation, the Swedish Brain Foundation, and the Swedish state under the ALF-agreement.